A new derivatization method for the determination of valproic acid in serum using tetramethylammonium hydroxide as a catalyst. (13th December 2018) - Mao, Guifu; Zhao, Kun; Sun, Shusen; Lu, Yanxia; Li, Xingang
Abstract: Valproic acid (VPA) pharmacokinetics is highly variable and monitoring of blood levels is necessary to determine its appropriate dosage. This study aimed to establish and validate a novel derivatization method for the determination of VPA. The method was based on the catalytic effect of tetramethylammonium hydroxide using 2, 4′‐dibromoacetophenone as a derivatization reagent. After derivatization, samples were injected into the HPLC system for analysis. The method showed a good linearity in the range of 1.0–200.7 μg mL −1, and the limit of quantification was 1 μg mL −1 . All values of the accuracy and relative standard deviations were acceptable for the analyses of biological samples. The recoveries were in the range from 91.6 to 97.4% for VPA with RSD <3.9%. A novel and high conversion‐rate derivatization method has been developed and validated for the determination of VPA in human serum. It can be applied to the analysis of VPA in clinic serum samples.